Metode Cultural Responsive Teaching dalam Pendidikan Agama Islam: Studi Kasus Tindak Xenophobia dan Rasisme di Tengah Bencana Covid-19 - Abadi, Mansurni; Muthohirin, Nafik (Pendidikan Agama Islam, 2020)
This article would like to explain the Cultural Responsive Teaching (CRT) approach in the learning of Islamic religion as an alternative effort to overcome the increase in xenophobia and racism action in the midst of the Covid-19. The method of extracting data is based on a literature review sourced from books, journals, mass media, and various expressions of racism and xenophobia that emerge on the homepage of Facebook, Twitter, WhatsApp groups, and other social media accounts. This paper will explain several important things, including CRT as an approach to see the diversity of cultures, ethnicities, religions, and groups; the meeting point of the CRT approach to the implementation of Islamic religious learning, and the elaboration between the two in voicing the importance of avoiding narratives based on racism and xenophobia.